Weight Perception, Weight Stigma Concerns, and Overeating. Issue 8 (28th June 2018) - Romano, Eugenia; Haynes, Ashleigh; Robinson, Eric
Abstract : Objective: Perceiving one's own weight status as being overweight is a likely motivation for weight loss. However, self‐perceived overweight status has also been found to be associated with overeating and weight gain. This study examined whether weight stigma concerns explain why individuals who perceive their weight status as overweight are at increased risk of overeating. Methods: We conducted two survey studies of United States adults ( N = 1, 236) in which we assessed whether weight stigma concerns explain the cross‐sectional relationship between perceived overweight and overeating tendencies. Results: Across two studies, the cross‐sectional relationship between perceived overweight and overeating tendencies was in part explained by weight stigma concerns. Participants who perceived their weight as "overweight" reported greater weight stigma concerns than participants who perceived their weight as "about right, " and this explained 23.3% (Study 1) to 58.6% (Study 2) of the variance in the relationship between perceived overweight and overeating tendencies. Conclusions: Weight stigma concerns may explain why perceiving one's own weight status as overweight is associated with an increased tendency to overeat.